Acute occlusion of an abdominal aortic aneurysm complicated by bilateral lower extremity venous thrombosis: A case report - Bridges, Kenneth G. (1981)
Acute occlusion of an abdominal aortic aneurysm is a rare phenomenon. Its possible complications include distal spasm followed by arterial thrombosis, ischemia of the distal limbs, distal embolization, acidosis, hyperkalemia, and the development of venous thrombosis of the lower limbs. Surgical correction is often complicated by cardiac decompensation, renal failure, fatal pulmonary embolism, and metabolic derangements related to toxins released from the revascularized limb. Unless contraindicated, immediate systemic heparinization must be undertaken when the diagnosis is first suspected. We present a case of sudden occlusion of an abdominal aortic aneurysm complicated by venous thrombosis involving both lower extremities. After undergoing surgical revascularization, the patient sustained massive fatal pulmonary emboli. Prophylactic interruption of the inferior vena cava may be indicated in patients who present with this complication of abdominal aortic aneurysm.